THE STUDY OF MEDICAL SCIENCE IN THE HERITAGE OF ORIENTAL SCIENTISTS - Alidjanova Lazizaxon Abbasovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Throughout the history of mankind, the issue of Medicine has never lost its relevance. It is especially at the center of the discussion that it should be based on religion or contradict religious teachings.